Preference, avoidance, motivation and their importance to fish welfare - Maia, Caroline Marques [UNESP]; Saraiva, João Luis; Gonçalves-de-Freitas, Eliane [UNESP] (Wiley, 2024)
Several studies have reported the neurophysiological and behavioural mechanisms that enable fish to experience several types of affective states, such as fear, pain and joy. This is crucial for the welfare feelings-based approach, as conditions that bring positive or negative valence to fish influence their affective state. A method to understand to what extent fish ‘like’ or ‘dislike’ their surrounding features is by evaluating their consistent choices (preferences) and propensity to reach environmental resources or traits (motivation). In this review, we propose how to assess preference and motivation tests in fish and discuss the limitations and potential biases that may affect such tests. Furthermore, we emphasize that understanding the avoidance responses of fish under a welfare context is a complementary method to improve the quality of life of fish in any type of rearing environment. Although there are other reviews about animal preference and motivation, this is the first one exclusively dedicated to the application of fish welfare.
Keywords: choices; environmental resources; environmental traits; positive/negative valence; Preference Index; rearing systems